Characterization of pulmonary impairment associated with COVID-19 in patients requiring mechanical ventilation - Virot, Edouard (Rev Bras Ter Intensiva, 2021)
OBJECTIVE: To detect early respiratory and hemodynamic instability to characterize pulmonary impairment in patients with severe COVID-19. METHODS: We retrospectively analyzed data collected from COVID-19 patients suffering from acute respiratory failure requiring intubation and mechanical ventilation. We used transpulmonary thermodilution assessment with a PiCCO™ device. We collected demographic, respiratory, hemodynamic and echocardiographic data within the first 48 hours after admission. Descriptive statistics were used to summarize the data. RESULTS: Fifty-three patients with severe COVID-19 were admitted between March 22nd and April 7th. Twelve of them (22.6%) were monitored with a PiCCO™ device. Upon admission, the global-end diastolic volume indexed was normal (mean 738.8mL ± 209.2) and moderately increased at H48 (879mL ± 179), and the cardiac index was subnormal (2.84 ± 0.65). All patients showed extravascular lung water over 8mL/kg on admission (17.9 ± 8.9). We did not identify any argument for cardiogenic failure. CONCLUSION: In the case of severe COVID-19 pneumonia, hemodynamic and respiratory presentation is consistent with pulmonary edema without evidence of cardiogenic origin, favoring the diagnosis of acute respiratory distress syndrome.